Análisis comparativo de los elementos comunicativos empleados para la construcción de la imagen política de las asambleístas Lucía Placencia Tapia y Johanna Ortiz Villavicencio en el periodo enero – marzo del 2021. - Calderón Ortiz, Viviana Mariuxi (2023)
The present research entitled: Comparative analysis of the communicative elements used for the construction of the political image of Assemblywomen Lucía Placencia Tapia and Johanna Ortiz Villavicencio in the period January - March 2021, had the purpose of conducting an analysis of the publications in the social networks Facebook and Twitter of the former Assemblywomen, given that, they managed to represent the province of Loja in the year 2021, placing themselves in important positions within the legislative branch. From the study of the posts made in their accounts, we identified the strategies they have used in social networks and how they have contributed to the formation of their political image. Through the application of non-participant observation forms, we were able to detail each element that was part of their posts, interviews were applied to structure a document where the most important features to take into account when managing the social networks of a politician were presented. It was concluded that the prevailing elements are: the linking of his name with the political movement, exposure of citizen support, disclosure of interviews in the media, as well as unfavorable elements such as the low percentage of publications on campaign proposals.